LncRNA NKILA: a killer regulator. Issue 11 (November 2018) - Bird, Lucy
The long non-coding RNA NKILA sensitizes antitumour T cells to activation-induced cell death. Targeting this pathway can improve adoptive T cell therapy for cancer.